Genomic Differentiation and Demographic Histories of Two Closely Related Salicaceae Species - Hou, Zhe; Li, Ang (Frontiers in Plant Science, 2022)
Abstract: Populus alba (P. alba) and Populus davidiana (P. davidiana) are important plant species for answering a variety of issues on species evolution due to their wide distribution and ability to adapt to a variety of environments and climates. Even though P. alba and P. davidiana belong to ecologically and economically important forest trees in the Northern Hemisphere, little is known about their genomic landscape and genome divergence during speciation. We re-sequenced 20 and 19 members of P. davidiana and P. alba respectively and found that the Dxy value between P. alba and P. davidiana was 0.2658, whereas the FST values were 0.2988, indicating that the genetic divergence was fairly clear. Populus davidiana and P. alba diverged from the ancestor in the middle Pleistocene, c. 0.80 Ma (95% HPD: 0.79–0.81 Ma). The population sizes of P. davidiana increased approximately 20,000 years ago after a considerable long-term decline following divergence. However, after differentiation, the effective population size of P. alba expanded slightly before experiencing a long-term bottleneck effect. According to the expectation of allopatric speciation, we found a significant number of genomic differentiation sites in both species' speciation events, and the majority of these genomic differentiation regions can be attributed to neutral evolutionary processes. Nevertheless, the regions with extreme divergence exist in abundance, indicating that natural selection has had an impact. Positive selection can be found in highly differentiated regions, while long-term balancing selection traits can be easily observed in low differentiated regions. According to these findings, climate differences over the Quaternary, as well as variance in linked selection and recombination, all contributed significantly to genomic divergence during allopatric speciation of the two aspens.